2020
DOI: 10.3389/fpsyg.2020.587757
|View full text |Cite
|
Sign up to set email alerts
|

Can Positive Affective Variables Mediate Intervention Effects on Physical Activity? A Systematic Review and Meta-Analysis

Abstract: Well-developed theories are necessary to guide the public in increasing physical activity (PA) and promoting physical health. The role of positive affective variables (PAVs) in exercise is gaining more attention, but none of the literature has provided a systematic review and quantitative analysis of its mediating role. Therefore, the purposes of this study are (1) to systematically review studies of PA interventions, that use PAVs as the mediating variables, in order to evaluate and provide narrative summarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 108 publications
0
23
0
1
Order By: Relevance
“…As reported in literature, enjoyment can be understood as an experience that reflects generalized feelings of pleasure, liking, and satisfaction, and may reflect an intrinsically motivational factor for participation in physical activity ( Moore et al, 2009 ; Nielsen et al, 2014 ). In several physical activity related contexts, enjoyment has presented positive associations with intention and adherence, as is the case for sports ( Nielsen et al, 2014 ; Granero-Gallegos et al, 2017 ; Teixeira et al, 2019 ), physical education ( Barr-Anderson et al, 2008 ; Gardner et al, 2017 ; Fin et al, 2019 ), exercise ( Chen et al, 2020 ; Klos et al, 2020 ; Rodrigues et al, 2020 ), and leisure-time physical activity ( Gardner et al, 2017 ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As reported in literature, enjoyment can be understood as an experience that reflects generalized feelings of pleasure, liking, and satisfaction, and may reflect an intrinsically motivational factor for participation in physical activity ( Moore et al, 2009 ; Nielsen et al, 2014 ). In several physical activity related contexts, enjoyment has presented positive associations with intention and adherence, as is the case for sports ( Nielsen et al, 2014 ; Granero-Gallegos et al, 2017 ; Teixeira et al, 2019 ), physical education ( Barr-Anderson et al, 2008 ; Gardner et al, 2017 ; Fin et al, 2019 ), exercise ( Chen et al, 2020 ; Klos et al, 2020 ; Rodrigues et al, 2020 ), and leisure-time physical activity ( Gardner et al, 2017 ).…”
Section: Introductionmentioning
confidence: 97%
“…In these multifactorial exercising interactions, promoting the dynamics that aim at enhancing the quality of the individual’s subjective experience can be challenging. For that matter, enjoyment was highlighted as a significant determinant of intention to continue and exercise adherence ( Nielsen et al, 2014 ; Calder et al, 2020 ; Chen et al, 2020 ). However, due to the intrinsic characteristics of the activities offered in health clubs, promoting exercisers enjoyment may not be easy.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, regarding the maintenance of PA, researchers emphasize the role of affective processes [10][11][12]. Notably, there is a large volume of studies describing the critical role of enjoyment in PA [13][14][15][16][17][18][19]. Despite extensive research demonstrating the importance of PA enjoyment, to date, however, there has been little consensus on what PA enjoyment actually is [20].…”
Section: Introductionmentioning
confidence: 99%
“…Following the upward spiral theory of lifestyle change, motivation is significantly associated with positive affects experienced during healthy behaviors, and motivational salience subconsciously guides attention to these behaviors and decisions to repeat them (van Cappellen et al, 2018 ). Further, a recent meta-analysis emphasized that the PAV emerges as a significant mediator between intervention and PA outcomes (Chen et al, 2020 ). Based on these neuroscientific, theoretical, and empirical fundamentals, enhancing PAVs is more likely to facilitate physical activity than activities that rely primarily on extrinsic motivation, such as those expected to improve health and well-being (Nielsen et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, we desired to exclude negative affective variables from this study (Egloff, 1998 ; Reich et al, 2001 ). The reasons were: (1) Reich et al ( 2001 ) conducted two experiments based on the two-factor model and the bipolar model, which showed that the cognitively more complex participants reported the mutual independence of positive and negative affect, while those with simpler cognitions reported the polarity of positive and negative affect, which meant that positive and negative affects could be differentiated for exploration; (2) as we described in the previous paragraph, the approach-avoidance distinction was also applicable in the affective variables; (3) Chen et al ( 2020 ) distinguished between positive and negative affective variables and demonstrated the significant mediating role of PAVs in the PA intervention. Overall, we would like to implement a more nuanced meta-analysis to understand how PAVs and PA can be manipulated in healthy populations.…”
Section: Introductionmentioning
confidence: 99%